Villa KBWW (Oz, 2003)
In this semi-detached villa on the Wilhelminapark in Utrecht the party wall functioned as a “therapeutic” compromise element during the dealings with the two client families. Both desired a spacious view of the park, optimal benefit from the sunshine, and a good relationship with the garden.